Adsorption of arabinogalactan-proteins from Acacia gums (senegal and seyal) and its molecular fractions onto latex particles. (April 2022) - Renard, D.; Davantès, A.; D'orlando, A.; Cahier, K.; Molinari, M.; Nigen, M.; Chalier, P.; Sanchez, C.
Abstract: Adsorption of Acacia gums (GA) (A. senegal and A. seyal ) and A. senegal molecular fractions, made of arabinogalactan-proteins (AGPs) with different molecular weights, onto latex particles, with different sizes and surface charges, was studied using molecular (fluorescence and nanoIR spectroscopies, microscopies including Atomic Force Microscopy) and mesoscopic (Dynamic Light Scattering, zeta potential, Asymmetrical flow field-flow fractionation) methods. Adsorption of GA onto latex particles revealed a complex mechanism of adsorption where the highest adsorption was observed when A. senegal and latex particles were negatively charged. The invert was observed for A. seyal where the maximum of adsorption was observed when gum and latex were oppositely charged. The duality of positive and negative charges on GA macromolecules together with conformational changes certainly explain the complex mechanism of adsorption. A mechanism where either the protein moiety either the sugars blocks adsorb is to be preferred. This mechanism seems to produce differences of behaviour due to viscoelastic properties of adsorbed layers, and differences of hydration due to differences of polarity of AGPs. The consequence of electrostatics in the adsorption process is a water release from the adsorbed layers and important gain in entropy. A fair agreement was found between protein content and adsorbed layer thickness of GA, with the formation of partial coverage, monolayer and multilayer films depending on GA concentration. Structural changes induced by GA adsorption onto latex particles was probed using fluorescence and nanoIR spectroscopies without giving clear evidence of conformational changes induced after GA adsorption. The results of this study highlighted that GA surface adsorption process depend not only on the protein moiety and electrostatic interactions but also on other parameters related to AGP hydration status. The protein structural accessibility, the molecular weight distribution, the AGPs intrinsic viscoelastic properties allowing structural rearrangements on the surface and spreading in order to form a viscoelastic film onto latex particles should also play a pivotal role in the adsorption process. Graphical abstract: NanoInfrared Atomic Force Microscopy reveals the successful functionalization of latex particles with Acacia gum ( Senegal and seyal ). Image 1 Highlights: Adsorption of Acacia gums onto latex particles with different sizes and surface charges was studied. The mass of GA adsorbed was often the highest in conditions of strong electrostatic repulsions. Electrostatic and hydrophobic effect mainly drive the adsorption process. Fluorescence and nanoIR did not give clear evidence of conformational changes induced after GA adsorption.